NHE-1 and NHE-6 Activities : Ischemic and Reperfusion Injury - Cingolani, Horacio Eugenio (2003)
The study published in this issue of Circulation Research showing that a null mutation of NHE-1 improves the tolerance of the heart to ischemia and reperfusion (I/R) is an important contribution for the following reasons: (1) In the animals with null mutation, contracture during the ischemic period was less and ATP levels were preserved compared with wild-type animals. This observation, on the one hand, provides evidence that protection by downregulation of NHE-1 during the ischemic period itself is indeed possible and, on the other hand, it argues against the suggestion that the exchanger is inactive during this same period. (2) In contrast with chronic blockade of the NHE-1 by pharmacological interventions, the long-term absence of the exchanger does not elicit major compensatory changes that, in turn, might negate the cardioprotective effect of blocking its activity for a relative short term. This point is related to a recent publication showing that long-term treatment with the NHE-1 blocker cariporide is followed by an upregulation of the functional units of the exchanger in a similar way to the well-known tolerance phenomenon following β-adrenergic receptor blockade. The absence of such upregulation negates possible hypersensitivity to ischemia upon withdrawal of the medication. The risk is evident in hearts with upregulation of NHE-1, which gain Na+i more rapidly during ischemia, and show impaired recovery after reperfusion. (3) No additional protection was obtained by adding the NHE-1 blocker eniporide to the NHE-1 null mice, suggesting that there is not another NHE isoform that can be blocked with this compound to add additional protection; the findings additionally hint that the attenuation of the injury obtained by the absence of the sarcolemmal NHE-1 is maximal and, therefore, no further beneficial effect will be detected by blocking the mitochondrial NHE (MNHE).